Political playthings for prostitute patriots. - (:unkn) unknown (Holland, William, 1791)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Burke, Edmund, 1729-1797; Great Britain -- Politics and government -- 1760-1820